Effect of Aluminum Chloride and Different Cryoprotectants on Hypertonic Cryohemolysis Development in Human Erythrocytes - Nardid, Ya. O.; Danilenko, N. A.; Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2005)
The peculiarities of development of hypertonic cryohemolysis of human erythrocytes at cooling from 37 down to 0Â°Ð¡under the influence of different cryoprotectors and aluminum chloride were investigated. It was istablished, that the presence of PEG-1500 and also aluminum chloride in the medium noticeably enhanced the stability of cells to temperature-osmotic effects. The use of penetrating cryoprotectors leads to increasing of hypertonic cryohemolysis level at the second stage of incubation in hypertonic conditions.